A novel security‐based adaptive reconfigurable intelligent surfaces assisted clustering strategy - Yue Tian; Xiaofan Zheng (Electronics Letters)
Abstract Reconfigurable intelligent surfaces (RISs) have attracted a great deal of interest due to the potential contributions to the next‐generation wireless networks. This letter proposes an enhancement to the physical layer security (PLS) of a multi‐hop RIS‐assisted underwater optical wireless communication (UOWC) system. Owing to the complexity of the underwater environment, a security‐based adaptive RIS (SA‐RIS) clustering strategy, which aims to reflect optical signals among clusters to improve the performance of the overall system, is evaluated. By combining the underwater channel model, the closed‐form expressions of probability density function (PDF) and cumulative distribution function (CDF) are derived. Moreover, by increasing the numbers of RIS clusters, the performance metrics such as secrecy outage probability (SOP) and average secrecy capacity (ASC) are evaluated under different scenarios. The obtained results demonstrated that, in contrast to the case without preventing the eavesdropper, the proposed strategy in evasion scenarios could improve the SOP significantly. It can be concluded that the system secrecy performances are further improved by assigning different RIS clusters with proper channel quality.